Efficacy and safety of cariprazine augmentation in patients treated with clozapine: a pilot study. (November 2022) - Pappa, Sofia; Kalniunas, Arturas; Sharma, Hitendra; Raza-Syed, Ali; Kamal, Manzar; Larkin, Fintan
Background: Cariprazine, a novel antipsychotic drug, is a partial agonist of dopamine D2/D3 receptors with preferential binding to the D3 receptor. There has been an increasing interest in cariprazine augmentation to clozapine; however, the evidence thus far has been only limited to case reports and case series. Objectives: To evaluate the efficacy and safety of the augmentation of clozapine with cariprazine in patients with sub-optimal treatment response. Methods: Demographic and clinical information of the study population were collected from the electronic records and PANSS scale administered at baseline and 3 months. Tolerability and discontinuation reasons where applicable were also recorded. Results: Ten patients (four men and six women) with a mean age of 36.5 years (range = 26–45) were included. Reasons for cariprazine initiation included inadequate treatment response, persistent negative symptoms and/or tolerability issues with clozapine or previous augmentation options. Two patients discontinued cariprazine within the first 6 weeks due to restlessness and poor response, respectively. There was a significant reduction in the median total PANSS score from baseline to 3 months (from 59 to 22.5, p < 0.05), median positive PANSS score (from 11.5 to 5.5, p < 0.05) and in the median negative PANSS score (from 15.5 to 3, p < 0.05) which correspond to a 48%, 33.8% and 65.8% mean score reduction, respectively. Conclusion: This is the first pilot study evaluating the effectiveness of clozapine augmentation. The preliminary evidence suggests that this may be a safe and effective practice in patients failing to adequately respond to or tolerate clozapine and/or previous augmentation strategies.